The ideas of N.I. Vavilov and current problems of crop genetics - Anisimova, Irina; Radchenko, Evgeny (Biological Communications, 2020)
Some results of the studies of plant genetic resources held in the VIR Department of Genetics are discussed in light of N. I. Vavilov’s theories of natural plant immunity, homologous series in hereditary variability, and interspecific hybridization. The long-term investigations resulted in identifying bread wheat, cultivated barley, oat, rye and sorghum accessions with new effective genes for resistance to diseases and pests. The large-scale immunological screening has revealed a narrow genetic diversity in wheat and barley for resistance to biotic and abiotic stressors. On the example of sunflowers, the significance of seed storage proteins for solving problems of domestication and introgressive hybridizations is demonstrated.